2021
DOI: 10.3390/ani11102864
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Stress in Rescued Wild Koalas (Phascolarctos cinereus) Being Held in a Rehabilitation Sanctuary: A Pilot Study

Abstract: Koalas (Phascolarctos cinereus) are one of Australia’s most charismatic native small marsupial species. Unfortunately, populations of koalas are rapidly declining throughout Australia as they continue to face increasing pressure from a changing ecosystem. All wildlife species to some degree will use their hypothalamic–pituitary–adrenal (HPA) axis in response to stress. Depending on the duration of activation, the stress response can lead to either acute or chronic side effects and is modulated through the neur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Implicit in our comparison is the assumption that the healthy, captive koalas were not experiencing chronic stress. Captivity can bring a range of potential sources of stress, including handling stress, frequent and loud noises, exposure to alien odours, restricted movement, isolation and the formulation of abnormal social grouping ( Morgan and Tromborg, 2007 ; Charalambous et al , 2021 ). A previous study compared the FCM concentrations of captive and wild koalas and found that the effects of captivity depended on sex and whether or not koalas were handled; handled male koalas had 200% higher FCM levels than their non-handled counterparts, and there was no difference between captive and wild koalas ( Narayan et al , 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Implicit in our comparison is the assumption that the healthy, captive koalas were not experiencing chronic stress. Captivity can bring a range of potential sources of stress, including handling stress, frequent and loud noises, exposure to alien odours, restricted movement, isolation and the formulation of abnormal social grouping ( Morgan and Tromborg, 2007 ; Charalambous et al , 2021 ). A previous study compared the FCM concentrations of captive and wild koalas and found that the effects of captivity depended on sex and whether or not koalas were handled; handled male koalas had 200% higher FCM levels than their non-handled counterparts, and there was no difference between captive and wild koalas ( Narayan et al , 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…The staff at the Magnetic Island Koala Hospital also observed and recorded any potential stressors encountered by the joeys. A range of stressors have been identified for marsupials in captivity [see Hing et al (2014), Hogan et al (2012), Charalambous et al (2021)], including (but not limited to) maintenance activities in and around the enclosure, moving animals to a different enclosure, visitor encounters, loud noises, extreme environmental events, handling for routine health checks and so on. This non-exhaustive list of potential stressors was used as a reference to observe and record potential stressors that could be affecting the koala joeys.…”
Section: Methodsmentioning
confidence: 99%
“…Cortisol is the principal GC produced by koalas (Narayan et al, 2013) and is increasingly acknowledged as a practical endocrine indicator of stress (Hing et al, 2014; Narayan & Williams, 2016). Whilst there have been a number of studies investigating the physiological stress response of marsupials (Cope et al, 2022; Hing et al, 2017; Hogan et al, 2011; Hogan et al, 2012; Narayan et al, 2012), including koalas (Charalambous et al, 2021; Pahuja & Narayan, 2023b; Webster et al, 2017), there is a paucity of literature on the capacity of koalas to respond to the stressors of captivity. In order to improve the rehabilitation outcomes and ensure the welfare of koalas in captivity, it is imperative to identify the potential stressors of captivity and understand how these animals respond to it.…”
Section: Introductionmentioning
confidence: 99%
“…Given the large number of animals entering rehabilitation, it is vital to identify aspects of the rescue and rehabilitation process that could pose animal welfare concerns or be targeted to reduce unnecessary distress and improve outcomes. The extent to which stress can impact the success of treatment and rehabilitation of wildlife is not known [44,45], however, some human medical studies have found that reducing stress improved treatment outcomes for cardiac patients [46][47][48], and it is known that stress can significantly alter wildlife immune function and survival [49].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study found that hedgehogs (Erinaceus europaeus) in rehabilitation had higher levels of faecal corticosterone metabolites and saliva corticosterone than wild hedgehogs [53], highlighting that GC responses could be associated with certain factors related to rehabilitation. A pilot study of koalas (Phascolarctos cinereus) in rehabilitation found that faecal glucocorticoids increased on days when a stressor was recorded in two of three studied koalas [45]. However, there is a lack of data for other animals that frequently enter rehabilitation, such as the brushtail possum.…”
Section: Introductionmentioning
confidence: 99%